A ligand oxidation structure-adaptive strategy for copper passivation - Liu He; Jingwen Huang; Wenzhen Zheng; Xiaoyu Song; Jie Liu; Huiqiang Lu; Xiaohui Liu; Birong Zeng; Yiting Xu; Conghui Yuan; Lizong Dai (Nature Communications)
Abstract Despite enormous efforts, copper corrosion remains a key inducement causing huge economic losses in electrical, construction, and military industries, and deteriorates the performance of semiconductor devices. Here we show that a set of ligands functionalized with both catechol and aromatic amine groups achieves environmentally-adaptive copper passivation and fully preserves the intrinsic electrical and thermal conductivities of copper and its alloys. The oxidation of ligands in corrosive environments causes the structure-adaptation of the passivation layer, further enhancing the corrosion resistance to harsh environments including alkali and salt solutions, thermal treatment, and UV-light- and oxygen-enriched conditions. Simply adsorbing these ligands on the surface of copper, brass, copper powder, copper-based flexible printed circuits, and copper inks for flexible electronics results in strong liquid and air anticorrosion performances. Our copper passivation technique only requires a room temperature soaking procedure, providing a high industrialization possibility for copper protection, particularly in semiconductor electronics and flexible electronics.